REPRESENTASI KEBAHASAAN DALAM TEKS BERITA SURAT KABAR (SEBUAH ANALISIS WACANA KRITIS) - Busri, Hasan (Diksi, 2009)
Representation is a strategy that journalists employ to present events in newsitems. Language expresses social functions and meanings in situational and culturalcontexts in society. This study employed phenomenology. The data sources were dailynewspapers Kompas, Jawa Pos, and Surya, which were randomly selected. The data werecollected through focused observations, theoretical and logical triangulations, andsnowballing. The researcher was the main instrument, equipped with a data codification,descriptive analysis guideline, explanatory analysis guideline, and data corpus table. Thedata were analyzed by using the descriptive and critical discourse analyses. The analysiswas interactive, involving reduction, display, and inference drawing (verification). Thestudy shows the following findings. (1) Vocabulary representation consists of associationand metaphor. (2) Grammar representation consists of process and participation. (3)Representation of clause combination or local coherence consists of elaboration,additional extension, contrast extension, optional extension, and heightening extension.Keywords: representation, news item, critical discourse